Tipologi Inovasi Pelayanan Pajak Daerah Melalui EPPSON di BPPKAD Kota Surakarta - Evita Dina Pratiwi; Kristina Setyowati (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
Tax is the main source of financing for state expenditures in order to improve people's welfare. Given the important role of taxes in the country's economy, in fact, there are still many problems and obstacles that must be faced in collecting local taxes in Indonesia. One of the efforts of the Surakarta City government to overcome this problem is through innovative technology-based local tax services in the form of the Electronic Solo Destination Tax Payment (EPPSON) feature. This study aims to determine the typology of local tax service innovation through EPPSON by using the typology dimension of innovation according to Perry, which consists of product innovation, service innovation, process innovation, conceptual innovation, policy innovation, and systemic innovation. The research method used in this research is descriptive qualitative, data collection techniques through interviews, observation, and documentation. The results showed that in its implementation, EPPSON innovation had met the criteria of product innovation, service innovation, process innovation, and systemic innovation. In addition, the EPPSON innovation has helped overcome local tax problems before the creation of this innovation.